Emilie Davis's Civil War : the diaries of a free Black woman in Philadelphia, 1863-1865 - Davis, Emilie Frances, 1838-1899 (The Pennsylvania State University Press, 2014)
"A transcription and annotation of the diary of Emilie Davis, a free African American woman who lived in Philadelphia during the Civil War"--Provided by publisher.